Guest Satisfaction Analysis Toward CHSE Implementation at Aston Braga Hotel and Rsidence Bandung. - Superwiratni; Imam Ardiansyah; Heru Kurniadi (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2021)
The purpose of this research is to determine the implementation of the CHSE that has been carried out by the management of Aston Braga Hotel and Residence in ensuring safety dan security for visiting guests. The research method of this research used quantitative research by giving questionnaires to respondents to assess the level of expectations and the level of perceived performance in the implementation of the CHSE using the Important Performance Analysis method. The sample used as respondents in this study were 331 respondents based on the number of guests who stayed in February 2021 using the Slovin formula. Based of research data result regarding Guest Satisfaction Index with the implementation of CHSE is 90.9% which have indicatesd “Very Good” criteria and for the IPA matrix, it is known that the indicators located in quadrants 1-4 need attention by management. Conclusions of this research obtained that the management of Aston Braga Hotel and Residence having a high commitment to service in the new normal era in implementing the CHSE so that the CHSE certification hopes to build trust in the community that the Indonesian tourism industry in the future will be rise.